2022
DOI: 10.1108/ejim-04-2022-0189
|View full text |Cite
|
Sign up to set email alerts
|

The impact of FDI technology spillover on the innovation quality of Chinese enterprises: a microperspective based on geographic proximity

Abstract: PurposePrevious studies have reached inconsistent conclusions on foreign direct investment (FDI) technology spillovers and corporate innovation. The main purpose of this paper is to explore the technological spillover effects of FDI from the microperspective of firm linkages induced by geographic distance. Further analysis is conducted on the impact and mechanism of this spillover on the innovation quality of Chinese enterprises. The conclusions drawn from this paper can guide Chinese enterprises' foreign capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…First, a neighbor country bene ts from reduced transport costs for manufactured consumables compared to a distant country. Second, the neighbor can obtain supplies for its infant industry at a lower cost thus attracting the spillover eect locally in terms of knowledge, innovation, information and support services (Harris, 1954;Liu et al, 2022;Yue et al, 2022;Amidi and Majidi, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a neighbor country bene ts from reduced transport costs for manufactured consumables compared to a distant country. Second, the neighbor can obtain supplies for its infant industry at a lower cost thus attracting the spillover eect locally in terms of knowledge, innovation, information and support services (Harris, 1954;Liu et al, 2022;Yue et al, 2022;Amidi and Majidi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…If these imports are consumables rather than capital goods from a nearby trade center giant, both shortrun and long-run growth may be negatively aected. Theoretically, it is not a matter of proximity rather proximity to a center country is what provides an additional spillover advantage, as observed with regard to FDI innovation and technology spillover to local enterprises in China (Yue et al, 2022). There is also evidence that spillovers in terms of policy diusion in proximal countries have been on the rise (Mossig et al, 2022).…”
Section: Source: Authors' Calculationmentioning
confidence: 92%
See 1 more Smart Citation
“…Lembcke and Wildnerova (2020) found that FDI tent to be associated with some growth in small firms from the study on 13 OECD countries. Yue et al (2022) found that FDI technology spillover has a positive impact on the innovation quality of MSMEs in China. Dimovski (2020) found that Macedonian MSMEs that cooperate with multinational enterprises have increased performance.…”
Section: Introductionmentioning
confidence: 97%
“…While the research on FDI's role on MSMEs growth is still limited, available research is generally supportive of the positive role of FDI (Islam & Chitakunye, 2019;Hernandez & Nieto, 2016;Yue et al, 2022;Li & Hu, 2013;Lembcke & Wildnerova, 2020). Islam and Chitakunye (2019) found that FDI is a significant factor for MSMEs growth strategies in the context of food industry in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%